KOMITE SEKOLAH MEMODERASI PENGARUH SUPERVISI, KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA TERHADAP KINERJA GURU (Students' Journal of Economic and Management, 2012)
This research aims to analyze the role of the School Committee Moderating Effect of Supervision Learning, Transformational Leadership and Culture School to Teacher Performance. The sample taken in this research as many as 96 people as respondents with a sensus method. With all of the criteria of a Junior High School Teacher District Kajen District. Pekalongan, has diversified III and S1 educated. Measurements using a Likert scale of 7 (seven) alternative answers. Test instruments used are validity and reliability. Classic asumptiont test making of normality test, heteroskedasticity test, and multikolinearity test. While the test model used is the coefficient of determination and F test (goodnes of Fit). Testing the hypothesis in this study using regression analysis.   The results showed the coefficient of determination (Adjusted R Square) of 0.200, meaning that supervision, Transformational Leadership, School Culture and School Committee together have 20% influence on Teacher Performance Junior High School as Kajen District District. Pekalongan and the remaining 80% are influenced by other variables not included in the study. Based on the results of the research can be summarized as follows: Learning Supervision does not have a positive and significant impact on teacher performance, transformational leadership is unknown impact on the performance of teachers, school culture does not have a positive and significant impact on the performance teachers, the school committee did not moderate the effect of learning supervision for the performance teachers, the School Committee moderating the effect of transformational leadership on teacher performance, the School Committee is unknown moderating the effect of school culture on teacher performance. Keywords: Learning Supervision, Transformational Leadership, School Culture and School Committee, and Teacher Performance